The utility of PET/CT with 18F-FDG in the study of Hodgkin's lymphoma and non-Hodgkin's lymphoma - Marta Milhões (Saúde & Tecnologia, 2015)
The lymphomas are tumors established in the lymphatic system. Due to their heterogeneity they can be classified as Hodgkin's lymphoma (HL) or non-Hodgkin's lymphoma (NHL), presenting each type of lymphoma, different prognosis and chemotherapeutic response. Currently Photon Emission Tomography/Computed Tomography (PET/CT) is considered as the "image" of excellence in the study of this pathology. In this context, it is of interest in this article to verify the usefulness of the PET/CT technique and to correlate the value of Standard Uptake Value (SUV) obtained by PET with the histological stage of lymphoma and the response to chemotherapeutic treatment. Methodology - We studied retrospectively 356 studies for 231 patients that did a PET/CT for staging, or evaluation of a mass or of the response to treatment. After administration of an average activity of 18F-FDG of 288.6 MBq, images were acquired on a PET/CT GE Discovery ST. These results were compared with clinical data of patients. Results - Significant differences were found between age vs type of lymphoma. No significant differences were found between: value of SUVmaxim nodes, extra-nodal lesions and their value of SUV for the type of lymphoma. It was verified the influence of PET/CT in the alteration of the stage of lymphoma as well as the therapeutic decision. Finally were found respectively the following values of sensitivity, specificity and accuracy: 98%, 79% and 88%. Conclusions - The results show the importance of imagingPET/CT in the evaluating the stage of the tumor and its role in monitoring and change of therapeutic decision.